57.9k views
3 votes
What is the value of 2(x + y) – (x – z) if x = 2, y = 1, and z = –3?

User Zerkey
by
4.9k points

2 Answers

5 votes
the answer would be 1 .. just plug in the numbers for the equation and do the parentheses first then distribute and add or subtract the rest of the numbers.
2( 2 + 1 ) - ( 2 - ( - 3 )
do the work inside the parentheses
2 ( 3 ) - ( 5 )
next you do 2 times 3 = 6
6 - 5 = 1
User NullByteMe
by
5.0k points
3 votes

Answer:

the answer is 1

Explanation:

User Mike Bartlett
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.